Study on the different arrangement of brick masonry wall between three type of bricks - Khairul Nusrat Kamal (School of Environmental Engineering, University Malaysia Perlis, 2013)
This project presents the result of brick masonry strength depends on different bonding follow by the type brick and to determine the crack pattern at the masonry wall.